2015
DOI: 10.3892/etm.2015.2311
|View full text |Cite
|
Sign up to set email alerts
|

Clinical potential of resistin as a novel prognostic biomarker for cellulitis

Abstract: Abstract. Cellulitis is an acute, subacute or chronic inflammation of the dermis and subdermal tissues, which is typically caused by bacteria, although other causes are possible. The present study aimed to evaluate the association between resistin levels and the recovery time of patients with cellulitis. In addition, the effect of resistin and insulin resistance on the prognosis of cellulitis was investigated. In total, 52 patients with cellulitis (male, 21; female, 31) and an age-matched group of 42 healthy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…There are some arguments for the importance of resistin as inflammation mediator in humans, such as the wellproven correlation between autoimmune diseases severity and resistin plasma level [42][43][44][45]. In normal pregnancy, resistin level in the pregnant women increases, therefore it can influence maternal-placental-fetal unit maturation [46].…”
Section: Discussionmentioning
confidence: 99%
“…There are some arguments for the importance of resistin as inflammation mediator in humans, such as the wellproven correlation between autoimmune diseases severity and resistin plasma level [42][43][44][45]. In normal pregnancy, resistin level in the pregnant women increases, therefore it can influence maternal-placental-fetal unit maturation [46].…”
Section: Discussionmentioning
confidence: 99%
“…Cellulitis is defined as inflammation affecting only the dermal and subdermal layers of soft tissue, while NF has deeper involvement affecting the superficial fascia and subcutaneous tissue. 31,32 The sonographic appearance of cellulitis is greatly dependent on the site and severity of the infection as the appearance can range from a diffuse swelling demonstrated by an increased echogenicity of the skin and subcutaneous tissue to a more variable cobblestone appearance, depending on the amount of fluid, degree of subcutaneous edema, and orientation of the interlobular fat septa. 33 A study conducted by Tsai et al 34 aimed to determine how cellulitis and NF can be differentiated on sonography and found that the sonographic findings of NF include: an irregularity of the fascia, an abnormal fluid collection along the fascial plane, and a diffuse thickening of the fascia when compared with the opposite limb, if unaffected.…”
Section: Imagingmentioning
confidence: 99%